PENGARUH ETIKA, PERILAKU, DAN KEPRIBADIAN TERHADAP INTEGRITAS GURU - Sri Sarjana; Nur Khayati (Jurnal Pendidikan dan Kebudayaan, 2017)
Integrity is one of requirements for teachers as a professional educator. Teachers with integrity is a role model for students. Strengthening teachers’ integrity is part of government policy to improving teacher quality in the future. The purpose of this study was to determine the effect of teachers’ ethics on teachers’ personality, the effect of teachers’ behavior on teachers’ personality, and the effect of teacher's personality on teachers’ integrity. This quantitative research developed explanatory survey method and the sample was 154 senior secondary school teachers in Bekasi district. Test of statistical data analysis using Structural Equation Modeling (SEM) with 8.8 Lisrel program and using SPSS 22. The results of this study shows that ethic and behaviour of teachers have a positive influence on their personality and it affects their integrity. Ethics and behaviour of teachers have an important role in improving the integrity through the development of the personality of the teacher. Efforts of teachers in improving their integrity is an essential need and it can be implemented through improving their ethics, developing their behaviour, and promoting their better personality.